2000
DOI: 10.1002/1097-0363(20000815)33:7<961::aid-fld39>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of coating flows with slip effects

Abstract: This work is concerned with the numerical prediction of wire coating flows. Both annular tube-tooling and pressure-tooling type extrusion-drag flows are investigated for viscous fluids. The effects of slip at die-walls are analysed and free surfaces are computed. Flow conditions around the die exit are considered, contrasting imposition of no-slip and various instances of slip models for die-wall conditions. Numerical solutions are computed by means of a time-marching Taylor Galerkin/pressure-correction finite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The implementation of such a boundary condition has customarily been followed in the literature as a means for avoiding singularities [28,29]. Newby and Chaudhury have experimentally confirmed that viscoelastic adhesives have larger slip zones than Newtonian liquids on segmentally mobile organic surfaces at and near crack tip regions [30].…”
Section: Problem Formulation-governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of such a boundary condition has customarily been followed in the literature as a means for avoiding singularities [28,29]. Newby and Chaudhury have experimentally confirmed that viscoelastic adhesives have larger slip zones than Newtonian liquids on segmentally mobile organic surfaces at and near crack tip regions [30].…”
Section: Problem Formulation-governing Equationsmentioning
confidence: 99%
“…In spherical coordinates, Eq. (13) boils down to r = −β(r)u r , where β(r) is the slip coefficient defined through β = 1/L slip with L slip denoting the (dimensionless) slip length (i.e., the size of the region near the contact line that slips); the no-slip case is recovered when L slip → 0 [28,29]. The consequences of such a slip boundary condition on bubble growth will be compared to those derived with the no slip boundary condition in Section 4.…”
Section: Problem Formulation-governing Equationsmentioning
confidence: 99%
“…This has accommodated model to complex flows exemplified through free-surface flows (Ngamaramvaranggul and Webster, 2000a), wire-coating (Ngamaramvaranggul and Webster, 2000b) and dough mixing applications (Baloch et al, 2002). Our present goal is to elaborate the constructive steps to incorporate weak-compressibility upon such a formulation, where we have polymeric liquid flow applications firmly in mind (viscous form, viscoelastic to follow).…”
Section: Pressure-correction Scheme -Compressible Flowsmentioning
confidence: 99%
“…Therefore, it comes as no surprise that the majority of numerical investigations relies on differential constitutive equations, using diverse numerical methods such as finite elements (e.g. [23,27,28,7], to cite only a few), finite volumes (e.g. [26,52]) and finite difference (e.g.…”
Section: Introductionmentioning
confidence: 99%